Assessing the Dimensional Validity and Reliability of the Critical Thinking Inventory (CTI) in the Kenyan Higher Education System: A Confirmatory Factor Analysis - Millicent A. Oyugi; Kristin Gibson; Alexa J. Lamm (Journal of International Agricultural and Extension Education, 2024)
The global importance of critical thinking in enhancing academic success, employability, civic engagement, and mental health is universally acknowledged. Yet, its cultivation in educational systems, particularly in Kenya, requires further attention. This gap is pronounced in Kenya's higher education, where more research is needed to develop and validate effective critical thinking assessment tools given the paradigm shift in its educational curricular. This study contributes to this need by evaluating the applicability of the Critical Thinking Inventory (CTI) model in Kenyan higher education. Using a convenience sample of 387 undergraduates from Egerton University, the study assessed the alignment between the CTI model, which measures information engagement and seeking, and observed variables in this context. The confirmatory factor analysis (CFA) results indicated a less-than-ideal fit (χ2(169) = 503.204, p < .000; CFI = .835; TLI = .795; RMSEA = .072), suggesting the need for further validation of the CTI model in this setting. Future research should extend to a more diverse and larger sample across various universities to improve the generalizability of these findings beyond a single institution. This study adds valuable insights into the critical thinking literature in higher education and highlights the need for ongoing research in Kenya. There is an evident necessity for future studies to focus on developing and validating contextually appropriate critical thinking assessment tools, following recommended validation procedures. Such efforts are crucial for a meaningful evaluation of critical thinking skills in the Kenyan competency-based educational system.
Keywords: Africa; critical thinking inventory; higher education in Kenya; assessment validation; confirmatory factor analysis